Analisis Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada UPT Wilayah III Pasar Klandasan Kota Balikpapan - Harianto, Rudy Pudjut; Haslinda, Haslinda (Fakultas Ekonomi Universitas Wisnuwardhana, 2018)
Abstract: This research aims to analyze the effect quality of services toward consumer satisfaction on UPT region III Klandasan traditional market. Several factors that can be considered in assessing a service given to consumers are reliability, responsiveness, assurance, empathy and tangible. This research used quantitative method with primary data sources and using simple random sampling method with 280 respondents.Data analyse method that used in this research are classical assumption test (normality, multicollinierity, heteroscedasticity, autocorrelation) and Multiple Linier Regression Analyse (correlation coeficient, determination coeficient, F test/varians analyse, t test/significantion test). Accumulatively, coeficient correlation (R) = 0,529 so that it can be said that the independent variables toward dependent variable in this research can giving the strong enough correlation. Result of Test Varians (F) express the Ho can be accepted because Fcount> Ftable or 21,272>2,247. Its meaning that variable of reliability, responsiveness, assurance, empathy and tangible by together did have the influence which significant to consumer satisfaction. The result of significantion test could be explained : (1) there are a significant effect of reliability on consumer satisfaction (2) there are a significant effect of responsiveness on consumer satisfaction (3) there are not a significant effect of assurance on consumer satisfaction (4) there are not a significant effect of empathy on consumer satisfaction, and (5) there are not a significant effect of tangible on consumer satisfaction. Keywords: reliability, responsiveness, assurance, empathy, tangible, consumer satisfaction.